Kualitas Manajemen Pelayanan SIM Oleh Satuan Fungsi Lalu Lintas Polres Kota Malang Jawa Timur - Shofwan, M.; Pribadi, Nukhan Wicaksana (Fakultas Ekonomi Universitas Wisnuwardhana, 2008)
administrative procedure judged good by the public, this issupported by the flowchart of the types and terms of service provisionin Polresta Malang SIM that can facilitate the community. But the rateof these procedures are too complicated. Complexity of servicesystems can be seen from the many requirements needed in one typeof service. To match between the fees paid by the specified fee, thecommunity is still assessing the cost paid too tinggi.Jaminan includeknowledge and courtesy of employees and its ability to giveconfidence to the community. These variables include employees whoare competent Polresta Malang, employee attitude, patience andfriendliness of employees, and employee behavior that may cause thetrust to the public. With competent employees in the field assures thepublic that their complaints can be quickly overcome and get asettlement. As for good behavior, patience and kind of employeesMalang Polresta able to give a sense of comfort and trust to the peopleof the problem at hand. In addition, people judge whether theemployee attitude that reflects the professionalism and courtesy.Employees who reflect the attitude of professionalism and politenesscan provide assurance to the public that the issue had to be resolved.Keywords: Quality, Service